Adventure Tourism and Outdoor Activities Management A 21st Century Toolkit - Jenkins, Ian S. (CABI, 2019)
An essential resource for those wishing to understand the driving factors behind the operation of an adventure tourism company, this textbook offers guidance on how to deliver a profitable and sustainable product. The importance of changing markets, technology and corporate social responsibility, including environmental impacts and climate change, are discussed in the context of managing an adventure tourism firm. To remain profitable, companies must address these issues along with the important aspects of risk and safety. Key features include Case studies from successful professionals in the industry, Consideration of the development of sustainable adventure tourism, Guidance on managing products and customers. Compiled from the author's experience in delivering adventure tourism courses over the last 20 years, this long-awaited book is aimed at both students taking university courses on adventure tourism and outdoor recreation as well as professionals working within the industry.